Inhibitory effect of harmane on morphine-dependent guinea pig ileum - ARICIOĞLU, FEYZA (NEW YORK ACAD SCIENCES, 2003)
Studies on the occurrence and properties of beta-carbolines structurally related to harmala alkaloids have gained attention since it was hypothesized that some of these compounds play a role in processes of substance abuse and dependence. This study investigates the effects of harmane on naloxone-precipitated withdrawal syndrome in morphine-dependent guinea pig ileum. Segments of ilea from starved male guinea pigs were obtained and fixed at a resting tension of 1 g in an organ bath containing 10(-6) M morphine in Tyrode solution at 37 degreesC, which was bubbled with 95% O-2 and 5% CO2. Tissues were incubated in 10-6 M morphine containing Tyrode solution for 4 hours before harmane was added. Naloxone and harmane had no effect on naive ilea. Naloxone (10-6 M) contracted morphine-dependent ilea. Harmane significantly inhibited the contractile response to naloxone in a dose-dependent manner (10(-7) M = 24%; 10(-6) M = 49.3 %; 10(-5) M = 70 %). These results suggest that harmane may have beneficial effects on morphine withdrawal syndrome.
Keywords: harmane; imidazoline; morphine dependence; ileum; NALOXONE-PRECIPITATED WITHDRAWAL; BETA-CARBOLINES; MONOAMINE-OXIDASE; RATS; HARMALINE; CLONIDINE; NORHARMAN